Anabolic Hormones Deficiencies in Heart Failure With Preserved Ejection Fraction: Prevalence and Impact on Antioxidants Levels and Myocardial Dysfunction - Bruno, Carmine; Silvestrini, Andrea; Calarco, Rodolfo; Favuzzi, Angela M. R.; Vergani, Edoardo; Nicolazzi, Maria Anna; d'Abate, Claudia; Meucci, Elisabetta; Mordente, Alvaro; Landolfi, Raffaele; Mancini, Antonio (Frontiers in Endocrinology, 2020)
Purpose. In heart failure with reduced ejection fraction, catabolic mechanisms have a strong negative impact on mortality and morbidity. The relationship between anabolic hormonal deficiency and heart failure with preserved ejection fraction (HFpEF) has still been poorly investigated. On the other hand, oxidative stress is recognized as a player in the pathogenesis of HFpEF. Therefore, we performed a cohort study in HFpEF aimed to 1) define the multi-hormonal deficiency prevalence in HFpEF patients; 2) investigate the relationships between hormonal deficiencies and echocardiographic indexes; 3) explore the modulatory activity of anabolic hormones on antioxidant systems. Methods. 84 patients with diagnosis of HFpEF were enrolled in the study. Plasma levels of N-terminal pro-brain natriuretic peptide, fasting glucose, insulin, lipid pattern, insulin-like growth factor-1, dehydroepiandrosterone-sulfate (DHEA-S), total testosterone (T, only in male subjects) were evaluated. Hormonal deficiencies were defined according to T.O.S.C.A. multi-centric study, as previously published. An echocardiographic evaluation was performed. Plasma total antioxidant capacity (TAC) was measured using the system metmyoglobin -H2O2 and the chromogen ABTS, whose radical form is spectroscopically revealed; latency time (LAG) in the appearance of ABTS● is proportional to antioxidants in sample. Results. Multiple deficiencies were discovered. DHEA-S deficiency in 87% of patients, IGF-1 in 67% of patients, T in 42%. Patients with DHEA-S deficiency showed lower levels of TAC expressed by LAG (meanSEM 91.259.34 vs 75.224.38 sec; p<0.05). No differences between TAC in patients with or without IGF-1 deficiency were found. A trend toward high level of TAC in patients without hormonal deficiencies compared with patients with one or multiple deficiencies was found. Regarding echocardiographic parameters, Left Atrial and Left Atrial Volume Index were significantly higher in patients with low IGF-1 values (meanSD 90.843.86 vs 72.833.78 ml; 51.032.33 vs 40.562.46 ml/m2, respectively; p<0.05) Conclusions. Our study showed high prevalence of anabolic deficiencies in HFpEF. DHEA-S seems to influence antioxidant levels; IGF-1 deficiency was associated with alteration in parameters of myocardial structure and dysfunction. These data suggest a role of anabolic hormones in the complex pathophysiological mechanisms of HFpEF and could represent the basis for longitudinal studies and investigations on possible benefits of replacement therapy.